Does gender and age at sexual initiation affect modern contraceptive use among teenagers and young adults in Nigeria? (2015)
This study was designed to assess use of Modern Contraceptive Use (MCP) among Sexually Active Teenagers and Young Adults (SATYA) as well as its determinants. We used a secondary data collected during the 2012 National HIV&AIDS and Reproductive Health Survey (NARHS Plus II 2012) in Nigeria. The cross-sectional and nationally representative survey adopted four-stage cluster sampling design. Bivariate and multiple binary logistic regression were used for data analysis at 5% level of significance. Females SATYA living in urban areas had higher odds of current use of MCP than those living in rural areas (OR=1.62(1.32-1.99)). The odds of current use of MCP among males that had sexual initiation between age 15 and 19 years and those that had it after age 20 years reduced by 21% and 36% respectively compared to males that were initiated before attaining age 15 years. The odds of using MCP currently among both males and females SATYA increased with higher economic status and educational attainment but more pronounced among females. Current use of contraceptive is general low among the youths but much lower among females than males who need it most. Although total abstinence from all sexual contact remains the surest way to avoid sexually related diseases and early child bearing as well as unwanted pregnancies, stakeholders should reenergize efforts towards use of contraception among sexually active teenagers and young adults.